Gower handbook of project management - Lock, Dennis (Gower, 1994)
The first edition of this handbook was published in 1987 under the title "Project Management Handbook", providing authoritative and comprehensive coverage of the subject. For this edition, the text has been revised and updated throughout to reflect recent developments. Eight new chapters have been added, dealing with such diverse topics as the impact of the European Community, project investment appraisal and environmental responsibility. A number of individuals and organizations have pooled their knowledge and experience to produce a practical treatment which ranges from first principles to some of the most advanced techniques now in use. It is suitable for anyone undertaking industrial or commercial projects.